GM1 - type 1 glanglio sido sis: anatomo-clinic study of a case - Ligia Maria Barbosa-Coutinho; Beatriz Maria Assis-Brasil; Maria de Lourdes Drachler; Newra Tellechea Rotta; Roberto Giuliani (Arquivos de Neuro-Psiquiatria)
The observation of generalized GM1 gangliosidosis type 1 (Norman-Landing disease) is reported. The case is typical, featuring all the main clinical and biological signs of the disease. Diagnosis was established by the demonstration of a severe deficit in beta-galactosidase activity in leucocytes, by the demonstration of oligosacarides in the urine, and by the histological examination after the fatal outcome before the age of two with severe respiratory distress.